Depression Of Annelies Reflected At Pramoedya Ananta Toer's Novel This Earth Of Mankind (1975): A Psychoanalytic Approach - Sari, Sobri Kartika; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
This study is about depression. The problem of this study is how the depression of Annelies reflected at Pramoedya Ananta Toer's novel This Earth of Mankind (1975). There are two objectives of the study; the first is to analyze the structural elements of the novel and the second is to analyze the character of Annelies based on psychoanalytic perspective of Sigmund Freud. In analyzing This Earth of Mankind, the researcher uses the psychoanalytic approach and qualitative method. The object of the study is This Earth of Mankind novel by Pramoedya Ananta Toer. In this research, there are two types of data, namely primary and secondary data. The primary data is the novel This Earth of Mankind itself, while the secondary data are taken from some information needed. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that this novel illustrates the condition of Indonesian in the Dutch Colonialism period. Second, based on the psychoanalytic approach the result shows that the depression is influenced by personality and anxiety.